METODE PEMBELAJARAN UNTUK MENINGKATKAN KESIAPAN SEKOLAH PADA PROGRAM PENDIDIKAN ANAK PRA-SEKOLAH - Ali Muhtadi (MAJALAH ILMIAH PEMBELAJARAN, 2010)
One of function of kindergarten education is to develop readiness of student in entering elementary school education. This function is important, remember research result indicates that children that follow kindergarten education shows achievement learns better in elementary school is compared to pupils that not follow kindergarten education (Wylie, 1998). To develop deftness that related to readiness of school, Muijs Reynolds (2008:280) say some key deftnesses that must passed to kindergarten child, that is: social deftness, deftness communicates, and deftness related to behaviour in task solution. As for some learning methods that applicable to develop deftnesses obove, that is: playing, cooperative learning, drama and short sandiwara, demonstration, discussion, problem solving, and mengategorisasikan object.